IMPLEMENTASI SKUA DAN PEMBENTUKAN SIKAP SPIRITUAL - Afifi, Mohammad (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2021)
This research aims to describe the additional religious material initiated by the Ministry of Religion of the East Java Regional Office which is packaged in the Ubudiyah and Akhlakul Karimah (SKUA) Proficiency Standards and its implementation process which is designed to contribute positively in shaping the spiritual attitudes of students at Madrasah Aliyah An-Najah I Sumenep. This research is categorized as a descriptive-qualitative field research with a naturalistic approach and case studies. The data analysis used interactive model analysis initiated by Miles and Huberman, namely: data reduction, data display, conclusion drawing and verification. The results showed that the content of this SKUA material was in accordance with the material content in the PAI subject cluster. In the implementation process, the implementation of SKUA learning at MA An-Najah I, it has gone through the ideal stages of implementing a standard curriculum, starting with planning then continuing with implementation and ending with the evaluation process. The spiritual attitude of students at MA An-Najah 1 is in a good category with the implementation of this SKUA.